Evaluation of the patient-based indices for orthodontic need assessment in the 13 to 18 year-old adolescents in Isfahan - maneh Asgari; Arezo Ebn Ahmady; Mohammad Hossein Khoshnevisan; Faezeh Eslamipour (Tehran University of Medical Sciences, 2012)
Background and Aims: Normative need assessments should be substituted or integrated by patient-based outcome measures regarding their shortages in health-oriented approach . This study aimed to assess and compare the ability of an index of oral health-related quality of life measured by Child Oral Health Impact Profile (COHIP) questionnaire and the Aesthetic Component of Index of Orthodontic Treatment Need (AC-IOTN) to identify the normative need to orthodontic treatment using Dental Health Component-IOTN in a sample of the Iranian adolescents.Materials and Methods: Target population of this cross-sectional analytic study was 597 of the 13 to 18 year-old schoolchildren enrolled in middle and high schools of the city of Isfahan, Iran. They completed the COHIP questionnaire and then were examined by two calibrated trained dentists (agreement coefficient:0.9) to record the DHC grading. The students scored their AC in according to the images of the scale. The association between subjective indicators and clinically defined need were evaluated by the correlation analysis and the statistics for the diagnostic validity of tests.Results: Of 568 examined students, 16.7% and 2.1% had definite need according to DHC and AC criteria, respectively. 10% of orthodontic patients had perceived distinct impact on their quality of life. The significant association (P=0.001) between the severity of malocclusion and quality of life was at moderate level by AC (R=0.37), but it was not convincing enough by DHC (R=0.16). The specificity of AC to detect the healthy ones showed to be excellent but its low sensitivity disabled the recognition of patients, precisely.Conclusion: The considered patient-based indices did not meet the competencies to define the orthodontic need in the adolescents, but it could be employed to identify the persons with impaired quality of life and it would probably benefit the process of prioritization.